Technology – pedagogy integration by pre-service teachers during internship programme: an analysis with special focus on Science Teaching - Sharma, Rashmi (Indian Journal of Educational Technology, 2020)
The quality of school education has a positive relationship with teachers’ training programme in the country. In the era of technological advancements, many strategies and pedagogical practices have been replaced by the technology driven practices. A reflection of this shift has been realized in most of the teachers training programmes; both; pre-service and in-service. However, the extent of integration of content with technology and pedagogy still needs to be studied in details. Also, there is a need to explore the ways of blending content, technology and pedagogy by the teachers in order to provide timely corrective measures. The paper analyses the current status of technological pedagogical content knowledge integration in four years integrated teachers training programme namely B.Sc. B.Ed. of Regional Institute of Education (RIE), Bhopal. It also recommends more synergy towards inclusion of technological pedagogical content knowledge (TPACK) in pre-service teachers training programmes besides suggesting ways for the same The analysis is based on lesson plan diaries of pre-service teachers maintained during internship period. Results of the study reflect that the pre-service teachers incorporate technology – pedagogy integration in the 30percent lessons during the internship programme. None of the pre-service teachers uses this integration for assessment purpose. Analysis reflects that the prospective teachers need to be made more equipped with the skills of technological pedagogical content knowledge integration. Also, TPACK should be a compulsory component in the curriclum of teachers training programme. At the end, paper discusses difficulties faced by pre-service teachers for integrating technology with pedagogy during their intership programme. Findings of the paper may be used for improvement of pre-sevice teachers training programme with respect to technology pedagogy integration.